EFFECTS OF SUPPLY CHAIN PROCUREMENT AND SUPPLY CHAIN AGILITY ON OPERATIONAL PERFORMANCE: THE MEDIATING ROLE OF DIGITAL TECHNOLOGY AT SOEKARNO–HATTA INTERNATIONAL AIRPORT - Lalita Veronika; Wahyuningsih Santosa*; Tri Wulandari Satitidjati Dewayana; Ranto Frederick Alexander (Universitas KH. Abdul Chalim Mojokerto, 2026)
The airport industry is characterized by real-time, complex, and high-intensity operations, making it highly dependent on supply chain reliability to maintain service continuity and operational performance. Soekarno–Hatta International Airport, as Indonesia’s primary national gateway, faces challenges related to increasing passenger volumes, growing operational complexity, and potential disruptions in the supply of critical assets and spare parts. This study examines the effects of supply chain procurement and supply chain agility on operational performance, with digital technology serving as a mediating variable. A quantitative survey was conducted with 268 respondents, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that supply chain procurement and agility have positive and significant effects on digital technology adoption and operational performance. Digital technology also significantly mediates these relationships. The study concludes that improving airport operational performance requires strengthening supply chain procurement and agility, integrated with the optimal utilization of digital technology.